Impact of federal funding for graduate medical education on residency program size: Evidence from the Affordable Care Act - Cici McNamara; Tehreem Hussain (PLoS ONE, 2025)
Primary care and rural physician shortages are a present and growing concern to policy makers. We assessed three Affordable Care Act (ACA) provisions that changed the maximum number of residents teaching hospitals could be reimbursed for, an element of graduate medical education (GME) funding known as the resident cap. The results show that an increase in a hospital’s resident cap of one slot under one of these ACA provisions in 2010 is associated with an increase in residency program size of approximately one full-time equivalent resident. We find important heterogeneity in the magnitude of the association between resident cap changes and program growth across ACA provisions, as well as in whether these associations are driven by changes in primary or non-primary care program growth. These results suggest that targeted changes to GME funding may be an effective tool in helping address physician shortages.